PEPTIDE-FUNCTIONALIZED MAGNETIC NANOPARTICLES FOR EARLY STAGE PATHOGEN DETECTION - Loso Judijanto; Vann Sok; Chenda Dara (Journal of Biomedical and Techno Nanomaterials, 2025)
The rapid and sensitive detection of pathogenic bacteria is paramount for preventing infectious disease outbreaks, ensuring food safety, and guiding clinical treatment. This study aimed to develop and validate a novel biosensing platform based on peptide-functionalized magnetic nanoparticles for the rapid, selective, and sensitive detection of a model pathogen, Escherichia coli O157:H7, in its early stages. Superparamagnetic iron oxide nanoparticles were synthesized and subsequently functionalized with a specifically designed, high-affinity peptide that targets an outer membrane protein of E. coli O157:H7. The detection was performed using a simple colorimetric assay based on the peroxidase-like activity of the MNPs, where the signal intensity was proportional to the concentration of captured bacteria. The peptide-functionalized MNPs demonstrated a high capture efficiency of over 95% within 20 minutes. The platform exhibited excellent sensitivity with a low limit of detection of approximately 15 colony-forming units per milliliter (CFU/mL) in buffer and 30 CFU/mL in spiked milk samples. The developed peptide-functionalized magnetic nanoparticle platform is a highly effective and robust system for the early-stage detection of pathogens. Its combination of speed, high sensitivity, and excellent specificity makes it a promising candidate for the development of portable, point-of-care diagnostic tools for applications in food safety, environmental monitoring, and clinical diagnostics, addressing a critical need for rapid and reliable pathogen screening.